THE EFFECTIVENESS OF GROUP GUIDANCE THROUGH TRADITIONAL GAMES IN IMPROVING INTERPERSONAL COMMUNICATION IN ORPHANAGE CHILDREN - Putri, Anggun; Muzaiyanah, Muzaiyanah; Putra , Bela Janare (Jurnal Konseling Pendidikan Islam, 2025)
This study investigates the effectiveness of group guidance through traditional games in improving interpersonal communication among orphanage children. The purpose is to determine the level of interpersonal communication before the application of traditional games and to assess the effectiveness of group guidance through traditional games for the children at the orphanage.This study uses a quantitative research method with an experimental design of one-group pretest and posttest. The population in this study consists of 18 children, with a purposive sampling technique selecting 12 children from the Amanah Rasal Orphanage. The results show that first, the TSR (high, medium, low) test revealed that the level of interpersonal communication (low) had a percentage of 92%. After the group guidance was applied through traditional games, the interpersonal communication level of the orphanage children increased to 75%. Secondly, from the paired samples T-test, the Asymp.sig (2-tailed) value was 0.000 < 0.005, meaning that Ha is accepted and Ho is rejected. There is a significant difference between the pretest and posttest results. Thus, it can be concluded that group guidance through traditional games is effective in improving interpersonal communication among orphanage children.